Prediction of Sorghum bicolor (L.) distribution ranges provides insights on potential sorghum cultivation across tropical ecoregions of Indonesia - Utomo, Suyud Warno; Lestari, Fatma; Adiwibowo, Andrio; Fisher, Micah R. (BMC plant biology, 2025)
Sorghum bicolor (L.) is a plant species that has staple and medicinal potential and is common in tropical regions, including Southeast Asia regions. Despite sorghum being used widely, the information about potential distributions of sorghum in various ecoregions in Indonesia is still limited. Indonesia is a vast country with distinct ecoregions, with wet ecoregions in western parts of Indonesia and arid environments in eastern parts. The information on sorghum potential distribution in various ecoregions is important, and in this situation, this study aimed to model the sorghum potential distribution in various ecoregions using MaxEnt based machine learning. The total area of Indonesia that is suitable for sorghum is estimated to be 68,527,000 ha, or 28.17% of Indonesia’s areas. Among all ecoregions in Indonesia, Sulawesi and Lesser Sunda, representing dry ecoregions, are having the largest suitable areas. The Lesser Sunda and Sulawesi ecoregions have the highest suitable percentages of 44.76% for Lesser Sunda and 21.53% for Sulawesi ecoregions. The lowest percentages were observed in the Sumatra, Kalimantan, and Papua ecoregions, representing wet ecoregions. This confirms that sorghum prefers the dry ecoregions, as high percentages of suitable areas are observed in these kinds of ecoregions.